Spinoff/Terminations and the Value of Pension Insurance - MARCUS, ALAN J. (Journal of Finance, 1985)
ABSTRACT This paper derives the value of Pension Benefit Guarantee Corporation (PBGC) pension insurance under two scenarios of interest. The first allows for voluntary plan termination, which appears to be legal under current statutes. In the second scenario, termination is prohibited unless the firm is bankrupt. Empirical estimates of PBGC liabilities are calculated. These show that prospective PBGC liabilities greatly exceed current reserves for plan terminations, that even under a bankruptcy‐only termination rule, PBGC liabilities still would be quite sensitive to discretionary funding policy, and that the increasingly common practice of pension spinoff/terminations, substantially increases the present value of the PBGC's contingent liabilities.